Research on the NOMA performance in cognitive cooperation network - Meiling LI; Ying LI; Muhaidat SAMI; Zengshou DONG; Anhong WANG; Jie LIANG; Liping DING (Tongxin xuebao)
The non-orthogonal multiple access (NOMA) technology was studied in a downlink cognitive relay cooperation network.A cognitive multiuser relay cooperation based NOMA scheme was proposed (CM-RC-NOMA),in which,the outage performance of PU and SU were given under different cognitive relay cooperation schemes and the corresponding outage expressions were also derived.At the same time,the AF based relay cooperation method and the DF based relay cooperation method were compared.The simulation results show that the lower outage of PU can be achieved by AF method compared with DF method,when the channel condition of BS to PU is no more than that of SU to PU.It is also revealed that the optimal outage performance of PU can be achieved by the proposed best cognitive relay cooperation scheme in contrast to the traditional best cognitive relay cooperation scheme.